Selective D3 receptor antagonism modulates neural response during negative emotional processing in substance dependence - Vamvakopoulou, Ioanna A.; Fonville, Leon; Hayes, Alexandra; McGonigle, John; Elliott, Rebecca; Ersche, Karen D.; Flechais, Remy; Orban, Csaba; Murphy, Anna; Smith, Dana G.; Suckling, John; Taylor, Eleanor M.; et al. (Frontiers in Psychiatry, 2022)
Introduction: Negative affective states contribute to the chronic-relapsing nature of addiction. Mesolimbic dopamine D3 receptors are well placed to modulate emotion and are dysregulated in substance dependence. Selective antagonists might restore dopaminergic hypofunction, thus representing a potential treatment target. We investigated the effects of selective D3 antagonist, GSK598809, on the neural response to negative emotional processing in substance dependent individuals and healthy controls. Methodology: Functional MRI BOLD response was assessed during an evocative image task, 2h following acute administration of GSK598809 (60mg) or placebo in a multi-site, double-blind, pseudo-randomised, cross-over design. Abstinent drug dependent individuals (DD, n=36) comprising alcohol-only (AO, n=19) and cocaine-alcohol polydrug (PD, n=17) groups, and matched controls (n=32) were presented with aversive and neutral images in a block design (contrast of interest: aversive>neutral). Whole-brain mixed-effects and a priori ROI analyses tested for group and drug effects, with identical models exploring subgroup effects. Results: No group differences in task-related BOLD signal were identified between DD and controls. However, subgroup analysis revealed greater amygdala/insular BOLD signal in PD compared with AO groups. Following drug administration, GSK598809 increased BOLD response across HC and DD groups in thalamus, caudate, putamen, and pallidum, and reduced BOLD response in insular and opercular cortices relative to placebo. Multivariate analyses in a priori ROIs revealed differential effects of D3 antagonism according to subgroup in substantia nigra; GSK598809 increased BOLD response in AO and decreased response in PD groups. Conclusion: Acute GSK598809 modulates the BOLD response to aversive image processing, providing evidence that D3 antagonism may impact emotional regulation. Enhanced BOLD response within D3-rich mesolimbic regions is consistent with its pharmacology and with attenuation of substance-related hypodopaminergic function. However, the lack of group differences in task-related BOLD response and the non-specific effect of GSK598809 between groups makes it difficult to ascertain whether D3 antagonism is likely to be normalising or restorative in our abstinent populations. The suggestion of differential D3 modulation between AO and PD subgroups is intriguing, raising the possibility of divergent treatment responses. Further study is needed to determine whether D3 antagonism should be recommended as a treatment target in substance dependence.